2019
DOI: 10.3892/mmr.2019.10079
|View full text |Cite
|
Sign up to set email alerts
|

Low‑frequency pulsed electromagnetic field inhibits RANKL‑induced osteoclastic differentiation in RAW264.7 cells by scavenging reactive oxygen species

Abstract: Bone homeostasis is a dynamic balance maintained by bone formation and resorption. An increase in the number and activity of osteoclasts leads to excessive bone resorption, which in turn results in bone disease, including osteoporosis. Therefore, inhibiting the differentiation and activity of osteoclasts is important for maintaining bone mass. Several studies have revealed that the use of a low-frequency pulsed electromagnetic field (PEMF) is an effective method to treat osteoporosis. However, its exact mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…In addition, this result is also supported by the studies of Osera et al [4] and Falone et al [5], showing that improving antioxidant response effect of short-and repeated PEMF pre-conditioning in drug-sensitive (SH-SY5Y) and drugresistant (SK-N-BE(2)) human neuroblastoma cell lines against pro-oxidant challenge by restraining H2O2-induced ROS production and increasing Mn-dependent superoxide dismutase (MnSOD) activity. The inhibitory effect of PEMF on intracellular ROS levels was also shown to inhibit osteoclastic differentiation [7,10]. Taken together, our findings could lay the framework for future research into the processes underlying the effects of post-exposed PEMFs at different doses, frequencies, and exposure conditions on intracellular ROS levels in neuronal signaling pathways, allowing us to reach a more thorough conclusion.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, this result is also supported by the studies of Osera et al [4] and Falone et al [5], showing that improving antioxidant response effect of short-and repeated PEMF pre-conditioning in drug-sensitive (SH-SY5Y) and drugresistant (SK-N-BE(2)) human neuroblastoma cell lines against pro-oxidant challenge by restraining H2O2-induced ROS production and increasing Mn-dependent superoxide dismutase (MnSOD) activity. The inhibitory effect of PEMF on intracellular ROS levels was also shown to inhibit osteoclastic differentiation [7,10]. Taken together, our findings could lay the framework for future research into the processes underlying the effects of post-exposed PEMFs at different doses, frequencies, and exposure conditions on intracellular ROS levels in neuronal signaling pathways, allowing us to reach a more thorough conclusion.…”
Section: Discussionsupporting
confidence: 54%
“…In certain bone modeling phases, ROS may activate osteoclasts while inhibiting osteoblasts [63]. By inducing ROS, ELF-PEMF thus may favor osteoclastogenesis, an assumption supported by the studies of Pi and Zhang [64,65]. However, there are also several other reports showing ELF-PEMF inhibitory effects on osteoclastogenesis [66][67][68].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 90%
“…This observation is in good agreement with the study of Pi et al, who showed that osteoclastogenesis decreased after the exposition of murine monocyte-macrophage lineage (RAW 264.7) to the low-frequency pulsed electromagnetic field and was associated with the lowered activity of TRAP. 37 In order to test the pro-osteogenic effectiveness of the scaffolds, we performed a bilateral cranial defect model in senescence-accelerated mouse prone 6 (SAM/P6) and evaluated the process of bone healing. Since SAM/P6 represents the model of senile osteoporosis with low bone mass and reduced bone mineral density, verification of clinical effectiveness using this model is fully justified.…”
mentioning
confidence: 99%